In vitro fermentation, digestibility and methane production as influenced by Delonix regia seed meal containing tannins and saponins - C. Supapong; A. Cherdthong; A. Seankamsorn; B. Khonkhaeng; M. Wanapat; S. Uriyapongson; N. Gunun; P. Gunun; P. Chanjula; S. Polyorach (My University, 2017)
1. Alemede I.C., Adama J.Y., Ogunbajo S.A., Abdullahi J., 2010. Haematological parameters of Savanna Brown does fed varying dietary levels of flamboyant tree seed meal. Pak. J. Nutr. 9, 167–170, https://doi.org/10.3923/pjn.20.... CrossRef Google Scholar
Keywords: African Botany and Ecology Studies